The effects of sustained forest use on hillslope soil hydraulic conductivity in the Middle Mountains of Central Nepal. Issue 2 (11th February 2013) - Ghimire, Chandra Prasad; Bruijnzeel, L. Adrian; Bonell, Mike; Coles, Neil; Lubczynski, Maciek W.; Gilmour, Don A.
ABSTRACT This work investigated the multi‐decadal changes in field saturated hydraulic conductivity, Kfs, beneath severely degraded pasture, natural forest and two mature planted Pinus roxburghii stands between two sets of measurements made in 1986 and 2011 at the same locations in the Middle Mountains of Central Nepal. Multiple measurements of Kfs were made at the four sites, both at the surface and at depths of 0·05–0·15, 0·15–0·25 and 0·25–0·50 m. The Kfs results were subsequently combined with rainfall intensities associated with different time intervals to infer multi‐decadal changes in dominant hillslope stormflow pathways. The widely assumed hydrological benefits of reforesting degraded land through the enhancement of near‐surface permeability due to such factors as the incorporation of a greater amount of organic matter, formation of macropores, as well as root development were not observed in this study. Continued heavy use of the natural and planted forests of the Middle Mountains, particularly the removal of understory vegetation and leaf litter, and cattle grazing, are considered to be the chief causal factors of the presently observed deterioration in forest hydrological functioning. This situation is typical not only of the Middle Mountain Zone across the Himalaya but is also observed in other densely populated parts of South and South‐East Asia. The key conclusion of this work is that simply planting trees in degraded landscapes is not sufficient in itself to restore watershed hydrological functioning. Attention also needs to be given to on‐going management of the reforested areas to balance product usage with watershed functions. Copyright © 2013 John Wiley & Sons, Ltd.